2020
DOI: 10.3389/fpls.2020.01043
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Two Aphid-Regulated β-1,3-Glucanase Genes by CRISPR/Cas9 Do Not Increase Barley Resistance to Rhopalosiphum padi L

Abstract: Callose deposition is induced in plants by various stress factors such as when plants are attacked by herbivores and pathogens. In the case of aphids, callose plugging of aphid-damaged phloem sieve tubes is expected to reduce aphid access to the phloem sap, while aphid-induced upregulation of callose-degrading β -1,3-glucanase genes in the host plant might counteract this negative effect on aphid performance. We have tested this hypothesis with barley mutants in which one or both of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020 ; Muthusamy et al, 2020 ), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020 ; Muthusamy et al, 2020 ), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020;Muthusamy et al, 2020), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Identification and Cloning Of Gtr Genes Sgrna Design And Vec...mentioning
confidence: 99%
“…Barley mutants with knocked out hvmorc1 further showed de-repression of transposable elements which could not be seen in the RNAi lines but was observed in the Arabidopsis mutants, demonstrating that different strategies to create mutants may result in distinct outcomes. Another study addressing pest resistance showed that combined knock-out of two of three aphid-induced beta-1,3-glucanase genes led to increased callose formation in leaves, however the effect did not lead to enhanced aphid resistance (Kim et al 2020).…”
Section: Wheatmentioning
confidence: 99%
“…Multiplexing approaches in barley have been carried out to increase the chance for disrupting a given gene or for the generation of fragment deletions at a particular locus (Kapusi et al 2017;Kapusi and Stöger 2018;Li et al 2020a;Zeng et al 2020a), or for the generation of double mutants at two loci (Gasparis et al 2018;Kim et al 2020). Different strategies were used to deliver the gRNAs: a polycistronic tRNA-sgRNA cassette (Gasparis et al 2018;Zeng et al 2020a), two conventional sgRNA cassettes on one vector (Kim et al 2020;Li et al 2020a) and mixing agrobacterium strains transformed with a vector containing each a single sgRNA cassette or, in the case of particle bombardment, co-bombardment of the two vectors (Kapusi et al 2017;Kapusi and Stöger 2018). The probability of isolating individuals edited at two or more target sequences results from the combined efficiencies of the sgRNAs.…”
Section: Barleymentioning
confidence: 99%
See 1 more Smart Citation